Blended learning during pandemic through knowledge management: an analytical study - Hasan, Khandakar Kamrul; Mostofa, Sk Mamun; Othman, Roslina; Mukherjee, Debarshi (World Scientific Publishing Co Pte Ltd, 2022)
Blended learning (BL) assimilates the best digital high-tech learning and traditional methods that involve students in network learning transcending physical boundaries. It has been embraced as a possibility so that knowledge can be distributed through time and space. KM-based approaches may be used to collect, coordinate, and transmit intelligence to control processes that can be utilized efficiently to recognize and share the most important details to address customer needs. This study aims to explain how to apply KM techniques in the BL environment to increase educational excellence and quality during pandemic situations. The specific consequences of BL actions are also stated in this paper. The quantitative approach was used in this study by using an electronic questionnaire from the students of the department of ISLM of the University of Dhaka, Bangladesh. Among the 272 students in the undergraduate program, 74 students replied to the online survey questionnaire. The gathered data were analyzed using SPSS version 20. The Findings of the study showed that KM can be used with BL during the COVID-19 pandemic, including integrated tasks, classroom instruction, online and e-learning. Finally, the study also proposed an intuitive model for applying BL through KM.